High frequency percussive ventilation and low FiO2 - Starnes-Roubaud, Margaret; Bales, Elizabeth A.; Williams-Resnick, Alex; Lumb, Philip D.; Escudero, Joe A.; Chan, Linda S.; Garner, Warren L. (Burns, 2012)
High-frequency percussive ventilation (HFPV) is an effective rescue therapy in ventilated patients with acute lung injury. High levels of inspired oxygen (FiO2) are toxic to the lungs. The objective of this study was to review a low FiO2 (0.25)/HFPV protocol as a protective strategy in burn patients receiving mechanical ventilation greater than 10days. A single-center, retrospective study in burn patients between December 2002 and May 2005 at the LAC+USC Burn Center. Demographic and physiologic data were recorded from time of admission to extubation, 4weeks, or death. 32 subjects were included in this study, 1 patient failed the protocol. 23 of 32 (72%) patients were men and mean age was 46±15years. Average TBSA burn was 30±20 with 9 of 32 (28%) having >40% TBSA involved. Average burn index was 76±21. 22 of 32 (69%) had inhalation injury and 23 of 32 (72%) had significant comorbidities. Average ventilator parameters included ventilator days 24±12, FiO2 0.28±0.03, PaO2 107±15Torr, PaCO2 42±4Torr, and PaO2/FiO2 ratio 395±69. 16 of 32 (50%) patients developed pneumonia and 9 of 32 (28%) died. No patient developed ARDS, barotrauma, or died from respiratory failure. There was no association between inhalation injury and mortality in this group of patients. A low FiO2/HFPV protocol is a safe and effective way to ventilate critically ill burn patients. Reducing the oxidative stress of high inspired oxygen levels may improve outcome.